2008
DOI: 10.1677/joe-07-0567
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine gland-derived vascular endothelial growth factor in rat pancreas: genetic expression and testosterone regulation

Abstract: Endocrine gland-derived vascular endothelial growth factor (EG-VEGF) is an endothelial cell mitogen, expressed essentially in steroidogenic cells. Recently, the expression of EG-VEGF in normal human pancreas and pancreatic adenocarcinoma has been demonstrated. Epidemiologically, pancreatic carcinogenesis is more frequent in males than females, and given that androgen receptors and testosterone biotransformation have been described in pancreas, we hypothesized that testosterone could participate in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(15 reference statements)
1
3
0
1
Order By: Relevance
“…Notably, the expression of EG-VEGF was also detected in the normal pancreatic islets. This phenomenon has also been observed in other studies (13,14). The positive expression of the EG-VEGF in the normal pancreatic islets suggests a function for EG-VEGF in the mediation of endocrine function.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, the expression of EG-VEGF was also detected in the normal pancreatic islets. This phenomenon has also been observed in other studies (13,14). The positive expression of the EG-VEGF in the normal pancreatic islets suggests a function for EG-VEGF in the mediation of endocrine function.…”
Section: Discussionsupporting
confidence: 86%
“…We found that testosterone down-regulates the mRNA of EG-VEGF in a dose response fashion, and the treatment with flutamide revert the effect [87]. The role of EG-VEGF in pancreas has not yet been completely established but in other steroidogenics cells and tissues, induces the proliferation, migration, and fenestration of endothelial cells, and has also been shown to act as survival factor modulating the growth of certain cells [88], it might be plausible then, that EG-VEGF produces similar effects in the pancreas.…”
Section: Effects Of Androgens On the Endocrine Pancreasmentioning
confidence: 73%
“…Since human pancreatic cells have steroidogenic activity, PK1 has been found to be expressed not only in normal pancreas but also in pancreatic adenocarcinoma (PC), where it is upregulated in islet cells, mainly in males, in the exocrine part, mainly in females, and in the blood vessels (Morales et al, 2007(Morales et al, , 2008. PC is characterized by poor vascularization and the presence of a large number of myeloid cells (Korc, 2007).…”
Section: Downloaded Frommentioning
confidence: 99%